Odpowiedzi

Najlepsza Odpowiedź!
2010-02-08T14:17:19+01:00
A) (-4)²+2³ = 16 +8 = 24
b) 3²-5² = 9 - 10 = -1
c) (-4)³-6² = -64 - 36 = -100
d) 8²-(-4)³= 64 + 64 = 128
e) -4²+(-3)⁴ = 16 - 27 = - 11
f) (-1) do potęgi 7-(-2)do potęgi 6 = -1-64 = -65

3 5 3
2010-02-08T14:19:55+01:00
A) (-4)²+2³=16+8=24
b) 3²-5²=9-25=-16
c) (-4)³-6²= -64-36=-100
d) 8²-(-4)³= 64-(-64)=64+64=128
e) -4²+(-3)⁴= 16+81=97
f) (-1) do potęgi 7-(-2)do potęgi 6= -1-64=-65
1 3 1
2010-02-08T14:24:31+01:00
A) (-4)²+2³ = 16+8 = 24
b) 3²-5² = 9-25 = -16
c) (-4)³-6² = -64-36 = -100
d) 8²-(-4)³ = 64-(-64) = 128
e) -4²+(-3)⁴ = 16+81= 97
f) (-1) do potęgi 7-(-2)do potęgi 6 = -1-64 = -65
1 4 1